Microbial diversity and methanogenic activity of Antrim Shale formation waters from recently fractured wells - Wuchter, Cornelia; Banning, Erin; Mincer, Tracy; Drenzek, Nicholas J.; Coolen, Marco J. (Frontiers in Microbiology, 2013)
The Antrim Shale in the Michigan Basin is one of the most productive shale gas formations in the U.S, but optimal resource recovery strategies must rely on a thorough understanding of the complex biogeochemical, microbial, and physical interdependencies in this and similar systems. We used Illumina Miseq 16S rDNA sequencing to analyze the diversity and relative abundance of prokaryotic communities present in Antrim shale formation water of three closely spaced recently fractured gas-producing wells. In addition, the well waters were incubated with a suite of fermentative and methanogenic substrates in an effort to stimulate microbial methane generation. The three wells exhibited substantial differences in their community structure that may arise from their different drilling and fracturing histories. Bacterial sequences greatly outnumbered those of archaea and shared highest similarity to previously described cultures of mesophiles and moderately halophiles within the Firmicutes, Bacteroidetes, and δ- and ε-Proteobacteria. The majority of archaeal sequences shared highest sequence similarity to uncultured euryarchaeotal environmental clones. Some sequences closely related to cultured methylotrophic and hydrogenotrophic methanogens were also present in the initial well water. Incubation with methanol and trimethylamine stimulated methylotrophic methanogens and resulted in the largest increase in methane production in the formation waters, while fermentation triggered by the addition of yeast extract and formate indirectly stimulated hydrogenotrophic methanogens. The addition of sterile powdered shale as a complex natural substrate stimulated the rate of methane production without affecting total methane yields. Depletion of methane indicative of anaerobic methane oxidation was observed over the course of incubation with some substrates. This process could constitute a substantial loss of methane in the shale formation.